Legal Authority of Navigation Districts in Ensuring Shipping Safety Based on Laws Regulations in Indonesia - Jemi Baransano; Muhammad Akhdharisa; Hadi Tuasikal (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to analyze the legal position, sources of authority, and legal responsibilities of Navigation Districts in ensuring shipping safety based on laws and regulations in Indonesia. The Navigation District as a technical implementation unit under the Directorate General of Sea Transportation holds strategic authority in the field of navigation that directly touches the safety of human lives at sea, but the legal framework that regulates its accountability is still considered inadequate. The method used is normative legal research with a legislative approach, studying materials Primary law includes Law Number 17 of 2008 concerning Shipping, Government Regulation Number 5 of 2010 concerning Navigation, and Regulation of the Minister of Transportation Number PM 67 of 2022, as well as secondary legal materials in the form of scientific journals and international conventions. The results of the study show that the authority of the Navigation District comes from the attribution of laws and regulations, but the existing regulatory framework contains the condition of lex imperfecta, which is the granting of large authority without being balanced by accountability and sanction mechanisms. This condition creates legal uncertainty for shipping service users while opening up potential liability demands in the dimension of international maritime law.